Policromia e soggettività nella filosofia di Hegel: i colori della storia e lo sviluppo dello spirito - Iannelli, Francesca (Revista Eletrônica Estudos Hegelianos, 2015)
It is renown that in a period of archeological uncertainty Hegel in accord with Winckelmann appreciated the pure white of the Greek statues. And it is also renown, that this assumption of the monochromy was completely contradicted by further studies. According to his philosophy of history Hegel saw in the ancient Greece just an inclination to subjectivity and in consequence refused to accept the possibility of polychromy in the Greek art. Greek sculpture as materialization of the Eternal denies the nuances and shades of colours, in other words Greek culture rejects the contradictions and ambiguities of the modern subject, but also his richness and multiplicity, because it is not deep enough to cope with this historical challenge.